Dowry and Inheritance, Gender and Empowerment in the ‘Notarial Societies’ of the Early Modern Greek World - Kasdagli, Aglaia E. (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2005)
This communication is something of a paradox. The project I am going to discuss here concerns an issue I have been working on for years, but on the other hand it is very much work in progress –and for technical reasons the progress is unfortunately much less advanced than I thought it would be when I first planned my contribution. First of all, the map illustrates what I mean by the term ‘notarial societies’ –mostly the world of the Greek islands – both along the western coast (Ionian islands) and the central Aegean (Cyclades and others), as well as in the south (Crete). The fall of Constantinople (1453) confirmed the Ottoman dominance on the major part of the former Byzantine Empire. However, some islands remained in Venetian hands or under various Latin lords affiliated with Venice (Khios with Genoa): major examples are Crete (until 1669), the Cyclades (to 1566) and the Ionian islands (to 1797). During the 17th century the Venetian presence was still strongly felt in the region. But the local population was – and remained – predominantly Greek in language and Greek Orthodox in religion. Those societies preserved the notarial tradition throughout the period and part of the vast amount of notarial acts has survived, throwing light on aspects of the social life about which there is very little evidence for the ‘non notarial’ parts of the region. Thus, the term ‘notarial societies’ designate those parts of the post Byzantine Greek world that preserved the medieval notarial tradition up to modern times. The extant notarial documents, therefore, outline the realities of populations, which in their majority shared a common language, religious creed and cultural (Byzantine) heritage. At the same time these were societies with differing physical characteristics, varying historical experiences, and different political and administrative framework, which moreover were subjected to variable cultural influences. All these factors are reflected in the significant regional variations that can be observed: take the example of the types of law regulating notarial practice, which offer a vital key for the interpretation of the information gleaned from the documents. At any given place the prevalent legal system might be any mixture of disparate elements: the Venetian law, in territories held by Venice; the customary law, which regulated most legal relations in regions like the Cyclades; and other influences, such as the feudal Frankish code used by the Latin rulers of formerly Byzantine lands; also, the canon law (which was in effect a continuation of Byzantine legal theory and practice) or the Islamic law, in places where Muslims had settled in large numbers.